Ethical Issues for Control-Arm Patients After Revelation of Benefits of Experimental Therapy: A Framework Modeled in Neuroblastoma - Unguru, Yoram (American Society of Clinical Oncology, 2013)
In 2009, the Children's Oncology Group (COG) phase III randomized controlled trial, ANBL0032, found that adding immunotherapy (Ch14.18) to standard therapy significantly improved outcomes in patients with high-risk neuroblastoma when administered within 110 days after autologous stem-cell transplantation (SCT). After careful deliberation and consultation, the COG Neuroblastoma Committee decided to offer Ch14.18 to prior trial participants who had been randomly assigned to the control arm (no immunotherapy), regardless of the time that had elapsed since SCT. This decision occurred in the context of a limited supply of Ch14.18 and no data regarding its role when administered beyond 110 days. In this article, we analyze the numerous ethical challenges highlighted by the ANBL0032 trial, including the limits of researchers' reciprocity-based obligations to study participants, post-trial access to beneficial therapies, and the balance between scientific knowledge and parental hope. These deliberations may be useful to other researchers when considering their ethical obligations to control-arm participants in the wake of a positive randomized trial.